2000
DOI: 10.2466/pms.2000.90.3c.1101
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Progressive Delay of Motor Development in Children with Sensorineural Hearing Loss and Concurrent Vestibular Dysfunction

Abstract: Gross motor development, and the effect of age, sex and vestibular function on it, was examined in 39 24- to 83-mo.-old children with sensorineural hearing impairment. Repeated testing was completed on 18 children. Delayed gross motor development was evident regardless of age, but only children less than 5 years of age had developmental balance deficits on initial testing. Both gross motor and balance development scores were lower on repeated testing. Furthermore, vestibular function scores facilitated identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
57
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(63 citation statements)
references
References 10 publications
1
57
0
2
Order By: Relevance
“…Additionally, are there individuals wherein a vestibular impairment present at birth goes undetected because of compensation or adaptation? Vestibular dysfunction has been implicated as a potential cause of delayed motor development in children (e.g., Takiguchi et al, 1991;Tsuzuku and Kaga, 1992;Admiraal and Huygen, 1997;Kaga, 1999;Rine et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, are there individuals wherein a vestibular impairment present at birth goes undetected because of compensation or adaptation? Vestibular dysfunction has been implicated as a potential cause of delayed motor development in children (e.g., Takiguchi et al, 1991;Tsuzuku and Kaga, 1992;Admiraal and Huygen, 1997;Kaga, 1999;Rine et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…It was determined that gross motor skill performance was not related to etiology of deafness or to the sex of the subjects. Rine et al (2000) also found evidence of delayed gross motor development regardless of age, but only children less than 5 years 1 of age had developmental balance deficits on initial testing. Both gross motor and balance development scores were lower on repeated testing.…”
mentioning
confidence: 83%
“…The cochlear and vestibular systems are anatomically and functionally connected, and so damage to either the cochlear or vestibular systems, or both, can lead to vestibular disorder and associated balance dysfunction (Rine et al 2000). In fact, impairment or absence of the labyrinthine righting reflex caused by vestibular dysfunction leads to a delay in gross motor and balance functions in children (Kaga 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, impairment or absence of the labyrinthine righting reflex caused by vestibular dysfunction leads to a delay in gross motor and balance functions in children (Kaga 1999). Previous studies have also demonstrated that children with hearing loss show a significant increase in center-of-pressure deviation and bodysway velocity measures made during a static standing balance test, and in the balance performance measure of the subsection item of the Bruininks-Oseretsky Test of Motor Proficiency (BOTMP), when compared to normal-hearing (NH) children (Gheysen, Loots, and Van Waelvelde 2007;Rine et al 2000;Siegel, Marchetti, and Tecklin 1991;Suarez et al 2007). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation